Determinants of perceived insufficient milk among new mothers in León, Nicaragua. Issue 3 (20th September 2016) - Safon, Cara; Keene, Danya; Guevara, William J. Ugarte; Kiani, Sara; Herkert, Darby; Muñoz, Erick Esquivel; Pérez‐Escamilla, Rafael
Abstract: Breastfeeding has been shown to improve maternal and child health. In Nicaragua, the primary risk of death and disability‐adjusted life years among children under 5 years of age is suboptimal breastfeeding. Although the Nicaraguan Ministry of Health promotes exclusive breastfeeding from within the first half hour through the first 6 months of life, less than a third of children in the country under 6 months of age are exclusively breastfed. As part of a larger, mixed‐methods study, 21 semi‐structured, in‐depth interviews were conducted with new mothers recruited from three primary health centers between June and August 2015 in order to identify the social, cultural, and structural factors that contribute to infant feeding practices and the discrepancy between recommendations and practices among mothers who delivered at an urban public hospital in León, Nicaragua. Audio recordings were transcribed verbatim, and interview transcripts were coded and analyzed by a three‐member team using a grounded theory approach. Findings highlight a widespread perception of insufficient milk among mothers that influenced early cessation of exclusive breastfeeding and other infant feeding practices. This perception stemmed from anxiety about meeting infant nutritional needs and infant satiety, anxiety about maternal nutrition, advice from and role modeling of family members about mixed feeding, and perceived infant feeding norms. Results suggest that support modeled after the 10 steps of the Baby‐friendly Hospital Initiative as well as strengthened policy‐level support are needed. Community interventions that address cultural and structural barriers to improve breastfeeding practices may also help to increase breastfeeding rates.